Cocirculation of Two env Molecular Variants, of Possible Recombinant Origin, in Gorilla and Chimpanzee Simian Foamy Virus Strains from Central Africa - Richard, Léa (J Virol, 2015)
Simian foamy virus (SFV) is a ubiquitous retrovirus in nonhuman primates (NHPs) that can be transmitted to humans, mostly through severe bites. In the past few years, our laboratory has identified more than 50 hunters from central Africa infected with zoonotic SFVs. Analysis of the complete sequences of five SFVs obtained from these individuals revealed that env was the most variable gene. Furthermore, recombinant SFV strains, some of which involve sequences in the env gene, were recently identified. Here, we investigated the variability of the env genes of zoonotic SFV strains and searched for possible recombinants. We sequenced the complete env gene or its surface glycoprotein region (SU) from DNA amplified from the blood of (i) a series of 40 individuals from Cameroon or Gabon infected with a gorilla or chimpanzee foamy virus (FV) strain and (ii) 1 gorilla and 3 infected chimpanzees living in the same areas as these hunters. Phylogenetic analyses revealed the existence of two env variants among both the gorilla and chimpanzee FV strains that were present in zoonotic and NHP strains. These variants differ greatly (>30% variability) in a 753-bp-long region located in the receptor-binding domain of SU, whereas the rest of the gene is very conserved. Although the organizations of the Env protein sequences are similar, the potential glycosylation patterns differ between variants. Analysis of recombination suggests that the variants emerged through recombination between different strains, although all parental strains could not be identified. IMPORTANCE SFV infection in humans is a great example of a zoonotic retroviral infection that has not spread among human populations, in contrast to human immunodeficiency viruses (HIVs) and human T-lymphotropic viruses (HTLVs). Recombination was a major mechanism leading to the emergence of HIV. Here, we show that two SFV molecular envelope gene variants circulate among ape populations in Central Africa and that both can be transmitted to humans. These variants differ greatly in the SU region that corresponds to the part of the Env protein in contact with the environment. These variants may have emerged through recombination between SFV strains infecting different NHP species.